Pembakaran Hutan dan Lahan Di Indonesia: Antara Hak Individu Vs Kepentingan Sosial terhadap Lingkungan Hidup - reinardus budi prasetiyo; Ansgarius Kase (Seminar Nasional Penelitian dan Abdimas, 2023)
Forest burning is part of environmental destruction whose impact can cause pollution or air pollution for humans. However, the burning of this forest occurs not only caused by natural factors but especially by the human factor seen from the theory of anthropocentrism considers that humans are the center of the universe and humans have the right to do anything to the environment and resources around it. Even though the sustainability of mankind itself is determined on the basis of the attitude it is currently doing for future sustainability. This paper seeks to explore the impact of burning forests and land in Indonesia with the aim of finding links with individual rights and social interests to the environment itself. This writing uses qualitative research methods with a normative approach where the source material used is the source of secondary and primary materials that are the reference for writing this study. In addition, what is important in this writing study is that the supervisory function and the role of the government in enforcing existing rules and regulations are challenges that until now have not been consistent with the problem of forest fires that occur. Keywords: Forest Burning, Individual Rights, Social Interests, Environment